Dilute Alkali Treatment as an Effective Strategy for Valorizing Young Coconut Coir as Cellulose Source - B. K. Wibowo; Y. A. Steefian; D. A. Stefani; D. Anggaran; Cahyanti, Margareta Novian (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Optimal utilization of the abundant young coconut coir has not been achieved, and not even an investigation into its potential as a source of cellulose has been conducted. Carbonized biomass and bioethanol are examples of energy carriers that can be produced from the cellulose found in young coconut coir. Additionally, cellulose can be utilized in the process of creating advanced materials like cellulose nanofibers and nanocrystals. In order to obtain cellulose from biomass, a treatment is required. The purpose of this study is to investigate how dilute alkali treatment affects the composition of young coconut coirs. Sodium hydroxide solutions at 1.5 and 3% concentrations were used in the alkaline treatment, which was carried out for one hour at room temperature and then for two hours at 100°C. The biomass-to-sodium hydroxide solution ratio was 1:24. The percentage of yield that is achieved following treatment with diluted alkali varies between 29.70 and 30.28%. Following treatment with 3% sodium hydroxide, the concentration of water-soluble compounds dropped from 45% to 3%. Following sodium hydroxide treatment, there was a decrease in the amounts of hemicellulose and lignin. Following a 3% alkali treatment, the cellulose content increased significantly from 19% to 66%. The significant increase in cellulose content after alkali treatment can be used to choose a treatment for young coconut coir during valorization.